PERENCANAAN AKTIVITAS KOMUNIKASI PEMASARAN DIGITAL PRODUK INDONESIA DI PASAR AMERIKA - Diana Lohita Wahyudi; Anabel Masyurah; Lydia Claudia Suwuh (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Planning of digital marketing communication activities for Indonesian products in the American market through social media marketing and websites to create and increase brand awareness. The United States is the largest consumer market in the world, with a household consumption expenditure value of USD 6.2 trillion in 2019. The majority of consumers in America prefer natural products because they have a high awareness of health. Veggie Noodle and Amphora Sumatra Coffee are the Indonesian products which have just entered the American market and at the moment these products are being marketed online through social media Instagram and Facebook, as well as websites. This nonthesis project aims to create and increase brand awareness of Indonesian products among American consumers. The planning of this work uses the SOSTAC concept (Smith, 2011) and applies a communication model (Sugiyama & Andree, 2011) to obtain reach in social media. This planning project is implemented on Veggie Noodle and Amphora Sumatra Coffee products which are exported to the American market by PT. Lohita International. This planning is expected to create and increase brand awareness of the two products above. The success of this planning project will be measured using metrics on social media and websites.